2016
DOI: 10.1002/slct.201601134
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses and Structural Analyses of New 3D Isostructural Zn(II) and Cd(II) Luminescent MOFs and their Application Towards Detection of Nitroaromatics in Aqueous Media

Abstract: Two new isostructural luminescent metal‐organic frameworks (LMOFs); {[M(BDC)(L)].xG}n, comprising Zn2+ (1) or Cd2+ (2) nodes, 4‐pyridyl carboxaldehyde isonicotinoylhydrazone (L), Benzene‐1,4‐dicarboxylic acid (H2BDC) and lattice guests (G) have been synthesized by diffusion, conventional and mechanochemical routes and thoroughly characterized. Single crystal structural analysis revealed doubly interpenetrating double pillared primitive cubic unit (pcu) structures with significant stability at ambient condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 102 publications
1
14
0
Order By: Relevance
“…In addition to the PET and RET mechanism, quenching behaviour is also supplemented by H-bonding interaction between the amide group of L 2 and the hydroxyl group of TNP via co-crystal formation. 69 In another example, two dimensional Cd(II) MOFs [Cd(5-BrIP) (TIB)] n (8) synthesized by our group using tripodal N-donor 1,3,5-tris(imidazol-1-ylmethyl)benzene (TIB) and 5-bromoisophthalate (5-BrIP) showed excellent photoluminescence properties in the solid state and in water. Fluorescence properties of the chemically stable ( 8) are exploited for the selective detection of TNP from a large pool of other nitroaromatics.…”
Section: Organic Pollutantsmentioning
confidence: 99%
“…In addition to the PET and RET mechanism, quenching behaviour is also supplemented by H-bonding interaction between the amide group of L 2 and the hydroxyl group of TNP via co-crystal formation. 69 In another example, two dimensional Cd(II) MOFs [Cd(5-BrIP) (TIB)] n (8) synthesized by our group using tripodal N-donor 1,3,5-tris(imidazol-1-ylmethyl)benzene (TIB) and 5-bromoisophthalate (5-BrIP) showed excellent photoluminescence properties in the solid state and in water. Fluorescence properties of the chemically stable ( 8) are exploited for the selective detection of TNP from a large pool of other nitroaromatics.…”
Section: Organic Pollutantsmentioning
confidence: 99%
“…A detailed structural analysis and physical characterization by using various analytical methods was performed on ZnMOF‐1 and ZnMOF‐2 synthesized by adaptable routes to elucidate the bulk phase purity. Crystallographic studies revealed that both ZnMOF‐1 and ZnMOF‐2 crystallized in a triclinic system in the P true1 space group and feature 3 D and 2 D frameworks, respectively, which were composed of Zn II metal nodes connected through dicarboxylate ligands and pillared by the Schiff base ligand (Figure a and c) . The 3 D framework in ZnMOF‐1 is constituted by 2 D [Zn 2 (bdc) 2 ] n secondary building units (SBUs) with a versatile coordination mode of the carboxylate group to generate sql (square lattice) nets, which are doubly pillared by L1 in the corresponding twofold interpenetrated pcu (primitive cubic lattice) type 3 D networks.…”
Section: Resultsmentioning
confidence: 76%
“…In this contribution, mixed‐ligand 3 D/2 D ZnMOFs {[Zn(bdc)( L1 )]⋅ x G} n ( ZnMOF‐1 ) and {[Zn(ipa)( L2 )]} n ( ZnMOF‐2 ) (in which H 2 BDC=benzene‐1,4‐dicarboxylic acid, L1 =4‐pyridyl carboxaldehyde isonicotinoylhydrazone, H 2 IPA=isophthalic acid, L2 =3‐pyridyl carboxaldehyde nicotinoyl hydrazone, and G=lattice guests) were synthesized by versatile synthetic routes, namely, a conventional reflux method and a green mechanochemical (grinding) reaction reported previously by us, and exploited for their potential as a catalyst in CO 2 fixation. The phase purity of bulk compounds synthesized by versatile routes was established by different analytical methods, and crystal structure analysis revealed 3 D and 2 D motifs in ZnMOF‐1 and ZnMOF‐2 , respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In past several decades, coordination polymers (CPs), as a class of multifunction materials assembled from organic multi‐carboxylic acid ligands and metal ions or clusters, have been obtained enormous attention because of their fascinating structural and interesting chemical properties, such as magnetism, gas storage, catalysis, drug delivery, chemical sensing, and other fields . Particularly, luminescent coordination polymers (LCPs) have been considered as excellent candidates to obtain high sensitive detectors for chemical sensing of metal ions, small organic molecules, explosives, and anions …”
Section: Introductionmentioning
confidence: 99%